2019
DOI: 10.5534/wjmh.180071
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Male Fertility: Effects on Assisted Reproductive Techniques

Abstract: During the last decades the study of male infertility and the introduction of the assisted reproductive techniques (ARTs) has allowed to understand that normal sperm parameters do not always predict fertilization. Sperm genetic components could play an important role in the early stages of embryonic development. Based on these acquisitions, several epigenetic investigations have been developed on spermatozoa, with the aim of understanding the multifactorial etiology of male infertility and of showing whether e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 76 publications
2
60
1
Order By: Relevance
“…This hypothesis is supported by the expression of IGF2 mRNA into human spermatozoa [24], and the homonym protein plays a role in prenatal fetal development. As a growth factor, IGF2 may play a role in the cellular mitosis of the embryo [25]. Furthermore, since the expression of IGF2 depends on the promotor methylation rate, which the embryo receives from the spermatozoon, it may be speculated that sperm-expressed IGF2 plays a role in embryo growth at the very early stage of embryo formation before EGA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This hypothesis is supported by the expression of IGF2 mRNA into human spermatozoa [24], and the homonym protein plays a role in prenatal fetal development. As a growth factor, IGF2 may play a role in the cellular mitosis of the embryo [25]. Furthermore, since the expression of IGF2 depends on the promotor methylation rate, which the embryo receives from the spermatozoon, it may be speculated that sperm-expressed IGF2 plays a role in embryo growth at the very early stage of embryo formation before EGA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence has shown that parental imprinted regions escape from demethylation, although the reason for this is not fully understood [23]. Some researchers hypothesized that paternally-expressed imprinted genes (e.g., IGF2, a sperm-carried transcript [24]) may be of particular importance in preimplantation embryo development [25]. Accordingly, the involvement of imprinted genes in embryo and placenta development and growth is well acknowledged in mice.…”
Section: Physiology Of Fertilization and Embryo Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Thousands of different RNAs (including coding and non-coding RNAs) have been detected in human spermatozoa [3]. As indicators of sperm transcriptional activity [4,5], RNAs in these cells likely derive from unmethylated or hypomethylated genes, which the transcriptional apparatus can access [1]. Several genes have been found to be differentially methylated in infertile patients compared to controls, and the most investigated pair of differentially methylated genes is H19/IGF2 [2].…”
Section: Introductionmentioning
confidence: 99%